사지에 발생한 혈관종의 수술적 치료 - 이수현(Soo Hyun Lee); 신규호(Kyoo-Ho Shin); 양우익(Woo-Ick Yang); 서진석(Jin-Suck Suh); 한수봉(Soo Bong Hahn) (The journal of the Korean Orthopaedic Association, 2004)
목 적: 사지에 발생한 혈관종의 치료로 절제술, 경피적 경화술, 방사선 조사 등이 시행되어 왔으나 결과에 대한 보고는 매우 드물어 혈관종을 수술적으로 치료한 결과를 분석하여 보고하고자 한다. 대상 및 방법: 1994년 1월부터 2001년 9월까지 혈관종으로 진단 받고 최소 1년 이상 추시가 가능하였던 80예를 대상으로 하였다. 남자가 31예, 여자가 49예였고 평균 연령은 22.1세였다. 수술적 절제술이 61예, 경피적 경화술은 9예에서 시행되었으며, 10예는 경피적 경화술과 수술이 시행되었다. 결 과: 수술적 치료를 받은 71예 중, 통증이 주 증상인 경우는 54예였고 이 중 49예에서 수술 후 통증이 완전히 소실되었으며 나머지 5예에서도 50% 이상 감소되었다. 크기는 평균 6×4 cm이었으며 5 cm 이상이 49예이었다. 재발은 4예(5.6%)에서 발생하였고 이중 3예는 경피적 경화술과 절제술, 1예는 절제술이 시행되었다. 수술적 치료가 필요한 합병증은 2예(2%)에서 발생하였다. 해부학적 진단으로는 해면상 혈관종이 51예(71.8%)로 가장 많았다. 경피적 경화술을 시행 받은 19예에서 평균 50% 정도의 통증 감소가 있었으며 경피적 경화술 또는 절제술 등의 다음 시술까지의 기간은 평균 1.5년이었다. 결 론: 혈관종의 치료에서 수술적 절제술은 통증의 감소 및 종괴의 제거를 위한 이상적인 방법으로 사료된다. Purpose: Hemangioma of the extremity is a painful soft tissue tumor. Many treatment modalities (surgical excision, sclerotherapy, radiation, etc) have been used, but results have rarely been reported. This study addressed the efficacy of surgical excision on hemangioma of the extremities. Materials and Methods: Eighty cases were analysed, all diagnosed as hemangioma between January 1994 and September 2001, and were followed up for at least 1 year. The male to female ratio was 31:49, and the mean age 22.1 years. Sixty-one of the cases received surgical treatment, nine cases sclerotherapy, and the other ten cases received both. Results: The main complaint of 54 of the 71 people who received surgery, was pain. After surgery, 49 were completely relieved of pain, and the reminder showed more than 50% pain relief. The mean size of the mass was 6×4 cm, and in 49 cases, it was larger than 5 cm. Hemangioma recurred in 4 patients (5.6%), 3 of the 4 received sclerotherapy and surgical treatment, only one received excision. Complications requiring surgical treatment occurred in only 2 patients (2%). The most common type was cavernous hemangioma which occurred in 51 cases (71.8%). Nineteen patients who received sclerotherapy showed reduced pain to about 50% average. Retreatment was required after a 1.5 years interval. Conclusion: Surgical excision is a reliable treatment for pain relief and for removing symptomatic hemangioma. KCI Citation Count: 4